2010
DOI: 10.1149/1.3313451
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Through Silicon Via Filling by Copper Electrodeposition

Abstract: High speed copper electrodeposition is needed to achieve the through silicon via ͑TSV͒ process with a high throughput. To inhibit electrodeposition on the top surface of the TSV, octadecanthiol ͑ODT͒ was microcontact-printed on the top surface. The ODT microcontact-printing effectively inhibits copper electrodeposition on the top surface. With sulfonated diallyl dimethyl ammonium chloride copolymer ͑SDDACC͒, V shapes were formed in the via cross section, and these shapes led to bottom-up via filling. We succee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 4 publications
0
36
1
Order By: Relevance
“…8,9 In addition, the convection dependent adsorption of leveler can make a steep gradient of surface coverage. [10][11][12] This disproportion of leveler adsorption results in the local enhancement of Cu growth at the bottom of a filling feature. The growing surfaces from the side wall meet each other, zipping up the features from the bottom, which is represented by V-shaped profile of Cu deposit.…”
mentioning
confidence: 99%
“…8,9 In addition, the convection dependent adsorption of leveler can make a steep gradient of surface coverage. [10][11][12] This disproportion of leveler adsorption results in the local enhancement of Cu growth at the bottom of a filling feature. The growing surfaces from the side wall meet each other, zipping up the features from the bottom, which is represented by V-shaped profile of Cu deposit.…”
mentioning
confidence: 99%
“…We have already reported that 10 μm diameter via of aspect ratio of 7.0 is perfectly filled within 37 minutes by using diallylamine leveler and oxygen gas bubbling (8,(12)(13)(14). By using a number of additives, such as chloride, SPS as accelerator, PEG as inhibiter and quaternary diallylamine as leveler, we enabled that the electrodeposition time have been shortened from 60 min to 35 min.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Copper is a good conductor but its coefficient of thermal expansion (CTE) is high. Therefore, issues related to CTE mismatch between the conducting materials and the dielectric materials arise in PCB and 3D packaging with high-density interconnections.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Recently, through-silicon vias (TSVs) have also been metallized by copper electroplating for the interconnection of threedimensional (3D) IC chip stacking packaging. [6][7][8][9][10][11][12][13] Copper is a good conductor but its coefficient of thermal expansion (CTE) is high. Therefore, issues related to CTE mismatch between the conducting materials and the dielectric materials arise in PCB and 3D packaging with high-density interconnections.…”
mentioning
confidence: 99%